A BLIND SPOT IN GIRLS' EDUCATION: MENARCHE AND ITS WEBS OF EXCLUSION IN GHANA. (29th April 2013) - Dolan, Catherine S.; Ryus, Caitlin R.; Dopson, Sue; Montgomery, Paul; Scott, Linda
Abstract Despite notable progress in girls' education over the last decade, gender‐based differences continue to shape educational outcomes. One of the most overlooked of these differences is the process of maturation itself, including menstruation. This paper presents the findings of a study that assessed the impact of sanitary care on the school attendance of post‐pubertal girls, as well as the implications of menarche for their well‐being. The study found that the provision of adequate sanitary care represents a relatively unrecognized but potentially fruitful tool in strategies that aim to improve girls' educational outcomes, one that warrants policy consideration among development planners. Copyright © 2013 John Wiley & Sons, Ltd.